The Potential of Developing Bread Fried Ciptamas Brand Identity to Increase Sales - Despianda S, Cheka Handi; Hardoyo, Adityo Baskoro (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This article aims to analyze the potentials for developing a brand identity for an UMKM product Roti Goreng Ciptamas. The method used in this research is a descriptive method that used to describe the elements of the product that can be further developed. The steps taken in this study were observations of the Roti Goreng Ciptamas product. Literature review used to determine the brand identity elements, and interviews with owners to find out visual considerations of the brand and the direction of business development planned by the owner. The owner has tried to give identity to his product by labeling it on the packaging and several other considerations that can give identity to the product. However, the concept of product presentation that is carried out by the owner of Roti Goreng Ciptamas is currently still focused on efficiency and cost-effectiveness. The result of this research is the discovery of elements in the Roti Goreng Ciptamas product that can be developed visually and the potential for developing the Roti Goreng Ciptamas business as a whole. The conclusions obtained are in the form of suggestions, especially to the owner of Roti Goreng Ciptamas regarding the considerations that need to be made to develop the brand identity of their products.